Challenging Case of Multisystem Inflammatory Syndrome in a 19- Year Old Female: A Case Report - Spasovska Vasilova, Adrijana; Rambabova Bushljetic, Irena; Milenkova, Mimoza; Canevska Taneska, Aleksandra; Gjorgjievski, Nikola; Pushevski, Vladimir; Shterjova Markovska, Zhaklina; Karanfilovski, Vlatko; Filipovski, Stefan; Severova Andreevska, Galina; Nikolov, Igor; Pavleska kuzmanoska, Svetlana; et al. (Macedonian Society of Nephrology, Dialysis, Transplantation and Artifical Organs, Department of Nephrology, 2022)
Introduction. In comparison to older adults, SARSCoV-2, leads to a mild illness in children and young adults typically manifested with fever, cough and gastrointestinal symptoms. However, the multisystem inflammatory syndrome in children and young adults (MISC) emerged during the coronavirus disease in 2019 pandemic. Case report. We report a challenging case of a 19- year old female patient with signs and symptoms of multisystem inflammatory syndrome and SARS-CoV2 infection, most probably as a post infectious disease with onset between 2 to 4 weeks after the infection. Its clinical symptoms may have overlaped with classical Kawasaki disease (systemic vasculitis) or Kawasakilike syndrome (atypical) with fever, gastrointestinal symptoms, rash, conjunctival injection, hypotension, sore throat, mucosal changes with a relative lack of severe respiratory disease, myocarditis, hypoalbuminemia and elevated inflammatory markers. And indeed, the clinical presentation of COVID-19 in young adults resembles Kawasaki disease with gastrointestinal manifestations to severe inflammation with myocarditis. Conclusion. Timely diagnosis and proper treatment of the multisystem inflammatory syndrome and SARSCoV-2 infection are real challenge requiring multidisciplinary approach and tertiary resources.
Keywords: coronavirus disease; young adults; pneumonia; pleural effusion; rash; Kawasaki like disease